Crossing Views on School and Non-School Learning The Javanese Village of Bejiharjo (Indonesia) and The Gypsy of Perpignan (France) - Sendra, Juliette; Fauziah, Puji Yanti (Journal of Nonformal Education, 2022)
This article proposes a reflection on the relationship between the school and its reference social environment based on two contexts: the Javanese village of Bejiharjo (Indonesia) and the gypsycommunity of Perpignan (France). In both places, there is a discrepancy in the logic of  action and value systems between formal and non-formal education. The educational goals put forward by national guidelines are not always in coherence with local and community educational logics. The school for these two populations is still generally perceived by families as an institution outside the village (knowledge and aims). This article therefore proposes to look at educational practises and family strategies for (non-) schooling of children within a broad educational context (school and non-school). It will also be a question of uncovering the relationships that are established between the modes of learning developed at school and out of school, both at the level of practice and at the level of the underlying aims. In the Javanese village of Bejiharjo, collective activities involving adults and children are organised in a collaborative manner, while at school the individual action of children is highly valued through competitions or championships, for example. In the gypsy community of Perpignan, learning outside school is based on forms of advanced autonomy or implicit solicitation of the child by the parents. School as a particular form of education brings into play exogenous norms and references within a given social context. We will therefore look at learning modalities and value systems as they emerge on these two terrains and examine how children adapt, negotiate and experience these dissonant logics between the school and non-school space.